Effect of Excessive Moisture and Heat on Seedling Establishment of Vegetable Pea - PRIYA NAIR; DHIRENDRA KHARE (Seed Research, 2026)
Vegetable pea is sensitive to excessive moisture for both germination and vigour index, therefore resulted in poor field emergence under inundation. To cover larger area under timely sown condition by flood irrigation, farmers may select varieties like AP 3, AP 1 or VRP 8. Arkel and PM 3 are sensitive to excessive moisture stress therefore pre-sowing irrigation should be adopted to obtain optimum plant population. Apart from excessive moisture, the crop also faces high temperature stress (28-35°C) when sown early in September. Varieties like Arka Sampurna, E6 and VRP 8 are more heat tolerant as compared to Arkel therefore can be recommended for early sown conditions.